The Prevalence of T Cells Population in the Liver of Patients with Viral Hepatitis - Tri Nugraha Susilawati; Triyanta Yuli Pramana; Brian wasita (The Indonesian Society for Digestive Endoscopy, 2020)
Background: It has been widely known that viral hepatitis is a major cause of liver disease that can cause chronic inflammation and carcinoma. This study aimed to describe the frequencies of CD4+ and CD8+ T cells, as well as regulatory T cells (CD25+ and Foxp3+ T cells) in the liver of patients with viral hepatitis in order to understand the comprehensive role of T lymphocytes in the progression of liver diseases attributed to viral hepatitis.Method: Liver biopsies were performed on adult patients presenting to a tertiary hospital in Surakarta, Indonesia with viral hepatitis from 2017 to 2018. Immunohistochemical staining was performed to identify cells expressing CD4+, CD8+, CD25+and Foxp3+ which represent T helper, T cytotoxic, and T regulatory cells, respectively. Additional data were retrieved from the patients’ medical records, including alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, viral load, and results of ultrasonography and fibroscan.Results: A total of 25 liver samples were collected from patients with chronic HBV infection (n = 21), chronic HCV infection (n = 2), acute HBV infection (n = 1), and from a with multiple liver nodules. The liver injury is minimum in all patients. The study found that CD8+ and CD4+ T cells were predominant whilst the frequency of T regulatory cells is generally low.Conclusions: The findings indicate the involvement of intrahepatic T helper and T cytotoxic in the pathogenesis of viral hepatitis. These liver infiltrating T cell subsets may be readily differentiated into regulatory T cells expressing CD25+ and Foxp3+ in order to prevent severe inflammation and maintain disease chronicity.